A Method for Signal Coordination in Large-Scale Urban Road Networks. (16th September 2015) - Ye, Bao-Lin; Wu, Weimin; Mao, Weijie
Abstract : Signal coordination methods have been widely investigated to improve the performance of traffic control system in urban road networks. Due to the large-scale of road networks and numerous time-varying parameters, a basic challenge faced by these methods is the high computational complexity. In this research, a method to optimize and coordinate the traffic signal in urban road networks is developed, which deals with this challenge by decomposing the network into several arterial roads and scattered intersections. As a result, an area coordination problem has been solved by coordinating several principal arterial roads and isolated intersections. Firstly, we propose a bandwidth oriented two-way arterial coordination approach. In contrast to previous methods, one important feature of the proposed approach is that not only the phases which provide right of way to the coordinated directions but the phases which provide right of way to the uncoordinated directions are considered. Secondly, to reduce the computational complexity a network decomposition approach is designed, in which a priority level index is defined to quantify the priority level of each road. Then, a coordination algorithm for the whole road network is developed. Finally, effectiveness and efficiency of the proposed method are validated by simulations on VISSIM.